Sultan Mahmud II dan Pembaruan Pendidikan di Era Turki Usmani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: As one of the sultan from Turki Usmani (Ottoman Turk) Empire, Mahmud II have conducted various renewal, especially in education. Mahmud II believe that one factor causing the decline of Usmani Empire is conventional education pattern (madrasah) which is only teach religious knowledge. By orienting at West, Mahmud II opens the new schools that teaching various modern science and send hundreds of student to various country in Europe. His effort brings successful fruit, namely emergence of innovators in various areas in Turki Usmani